Validation of the ISGLS classification of bile leakage after pancreatic surgery: a rare but severe complication - Mehrabi, Arianeb; Abbasi Dezfouli, Sepehr; Schlösser, Fabian; Ramouz, Ali; Khajeh, Elias; Ali-Hasan-Al-Saegh, Sadeq; Loos, Martin; Strobel, Oliver; Müller, Beat P.; Berchtold, Christoph; Mieth, Markus; Klauß, Miriam; et al. (European journal of surgical oncology, 2022)
Introduction - Hepaticoenterostomy is an important step of reconstruction during hepatopancreatobiliary (HPB) surgery with a subsequent bile leakage rate of up to 5%. The International Study Group of Liver Surgery (ISGLS) proposed a severity grading system for defining bile leakage after HPB surgery, which has not been validated after pancreatic surgery in a large patient cohort. The present study aimed to validate the ISGLS definition for bile leakage in pancreatic surgery and to investigate the postoperative outcomes of bile leakage after pancreatic resections. - Materials and methods - Data from the prospectively maintained database for pancreas surgery were extracted for any type of pancreatectomy with hepaticoenterostomy between 2006 and 2019. The severity of bile leakage was graded according to the ISGLS definition. The influence of our standardized hepaticoenterostomy technique and of the complexity of the surgical procedure on the rate of clinically relevant bile leakages (B and C) were assessed in three different timeframes. - Results - Bile leakage was detected in 152 of 5,300 patients (2.9%). Clinically relevant bile leakages included seventy patients with grade B and eighty-two patients with grade C bile leakages (46.1% and 53.9%, respectively). During the study period, the overall rate of bile leakage showed to be stable (from 3.5% to 2.4%). Patients with grade C bile leakage had a higher rate of postoperative wound infection (P < 0.001) and longer ICU stays and hospital stays compared to patients with grade B bile leakage (P = 0.03 and P < 0.001 respectively). These parameters were significantly higher in patients with late grade C bile leakage but were similar between patients with grade B bile leakage and early grade C bile leakage (<5th day POD). In the whole patients’ cohort, the 90-day mortality rate was 3.2% (174/5,300), with a rate of 25% in patients with bile leakage (38/152). - Conclusion - The ISGLS classification is a valid method for classifying postoperative bile leak after pancreas surgery. Standardization of our hepaticoenterostomy technique resulted in a stable rate of bile leakage. Although rare, bile leakage following pancreas surgery is a severe complication that has a major impact on patient outcomes and contributes significantly to morbidity and mortality, even in the absence of POPF.
Online verfügbar 24 Juni 2022
Gesehen am 14.03.2023